Når faglig status ikke kan tages for givet: En analyse af social- og sundhedselevers individuelle kampe for professionel anerkendelse - Jensen, Maya C. Flensborg (Tidsskrift for Professionsstudier, 2025)
The demographic development has increased the demand for social and health professions (SOSU), but these professions remain difficult to recruit for and have low status despite professionalization. Based on focus groups with a total of 31 SOSU students, the article examines how the students legitimize their choice of profession and handle the devaluing perceptions they encounter in society. The analysis shows that the students develop professional ideologies in which they either reframe or refocus away from the less valued aspects of the profession. Through reframing, work with the elderly and personal care is ascribed new value, while refocusing shifts attention to work in hospitals and roles as ’junior nurses.’ The article discusses how these ideologies contribute to understanding the causes of the care crisis and highlights both the potentials and dilemmas in the students’ professional worth attribution.